Therapeutic Approaches for Nonalcoholic Fatty Liver Disease: Established Targets and Drugs - Huang X; Chen H; Wen S; Dong M; Zhou L; Yuan X (Diabetes, Metabolic Syndrome and Obesity, 2023)
Xiaojing Huang,1,2 Huiling Chen,2 Song Wen,2 Meiyuan Dong,2 Ligang Zhou,2 Xinlu Yuan2 1Graduate School of Fudan University, Shanghai, People’s Republic of China; 2Department of Endocrinology, Shanghai Pudong Hospital, Fudan University Pudong Medical Center, Shanghai, People’s Republic of ChinaCorrespondence: Xinlu Yuan, Department of Endocrinology and Metabolic Diseases, Shanghai Pudong Hospital, Fudan University Pudong Medical Center, Shanghai, People’s Republic of China, Email yuanxinlu1982@126.comAbstract: Nonalcoholic fatty liver disease (NAFLD), as a multisystemic disease, is the most prevalent chronic liver disease characterized by extremely complex pathogenic mechanisms and multifactorial etiology, which often develops as a consequence of obesity, metabolic syndrome. Pathophysiological mechanisms involved in the development of NAFLD include diet, obesity, insulin resistance (IR), genetic and epigenetic determinants, intestinal dysbiosis, oxidative/nitrosative stress, autophagy dysregulation, hepatic inflammation, gut-liver axis, gut microbes, impaired mitochondrial metabolism and regulation of hepatic lipid metabolism. Some of the new drugs for the treatment of NAFLD are introduced here. All of them achieve therapeutic objectives by interfering with certain pathophysiological pathways of NAFLD, including fibroblast growth factors (FGF) analogues, peroxisome proliferator-activated receptors (PPARs) agonists, glucagon-like peptide-1 (GLP-1) agonists, G protein-coupled receptors (GPCRs), sodium-glucose cotransporter-2 inhibitors (SGLT-2i), farnesoid X receptor (FXR), fatty acid synthase inhibitor (FASNi), antioxidants, etc. This review describes some pathophysiological mechanisms of NAFLD and established targets and drugs.Keywords: non-alcoholic fatty liver disease, oxidative stress, lipotoxicity, organ dysfunction, dysbiosis, new treatment modalities